Perancangan Strategi Berdasarkan Analisis Pengaruh Rasio Keuangan dan Rasio Pasar terhadap Harga Saham (Studi Kasus pada Perusahaan Indeks IDX30 di Bursa Efek Indonesia Tahun 2016-2022) - Nurrahman, Ahmad Rizky; Chumaidiyah, Endang; Zulbetti, Rita (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Investment has played a crucial role in driving Indonesia's economic growth post Covid-19 pandemic, notably contributing to the IDX30 index and witnessing a rise in investor numbers. The aim of this study was to uncover trends and the influence of financial and market ratios on stock prices, both concurrently and partially. Another aim also offers recommendations for investors and companies to optimize investment benefits and enhance future corporate performance. The sample for this research comprises 9 companies listed in the IDX30 index for the years 2016-2022. The data utilized encompasses secondary data, processed using panel data regression, and primary data collected through an AHP questionnaire. The findings of this study revealed that trends of ROE, CR, PBV, and HS show a decreasing trend, while DER and EPS indicate an increasing trend. ROE, CR, DER, EPS, and PBV collectively exert a significant impact on stock prices. Furthermore, partial effects showed that ROE, EPS, and PBV significantly affect stock prices. Enhanced performance strategies for companies, both internally and externally, are formulated using IFAS and EFAS, followed by their integration into a SWOT matrix. These results are used to recommend strategies for investors and companies to optimize investments and overall corporate performance.